Remittances: Development Impact and Future Prospects - Maimbo, Samuel Munzele; Ratha, Dilip (Washington, DC: World Bank, 2012)
Remittances explores policy options for enhancing the poverty alleviation impact of remittance money in recipient countries, and addressees concerns about increasing migration and inequality. It looks at new technologies that allow remittance service providers to reduce direct transaction costs and open new channels, enhancing convenience for remitters and improving levels of transparency and accountability for regulators and policy makers. Importantly, it also establishes a baseline for further research and collaborative effort, showing the areas where the international financial institutions, particularly the World Bank, can add value to enhance the positive impact of remittance flows and minimize less welcome effects.